Coleta e sistematização de dados geológicos da Folha Santa Quitéria (SB-24-V-B-I) Região Central do Ceará. - COSTA, Vedrana Celi Lima (2018)
Basic geological mapping is an activity that in Brazil will last for many years, since the country has just reached the 30% of its territory mapped in the 1: 250,000 and 1: 100,000 scales. A complementary geological mapping in the 1: 100,000 scale was carried out in the Sheet, in part of the uncovered areas with a focus on the description of outcrops, emphasizing its lithological and structural aspects accompanied by the systematic collection of samples for petrographic studies. The study area is located in the geological context of the Central Ceará Domain (DCC), Borborema Province. Its geological evolution is strongly related to the formation of the Tamboril-Santa Quitéria Complex, which, according to Fetter et al. (2003), probably represents a remnant of the Brasilian continental arc. The treatment of the data obtained in the field together with the petrographic analyzes of the collected rocks allowed us to propose that the gneisses of the Tamboril-Santa Quitéria complex (hornblende-biotite gnaisse and muscovite-biotite gnaisse) are predominantly or- derdered and reached their paragenesis around 550- 750 ° C (amphibolite facies) in a regional metamorphism system. This process was accompanied by the neoproterozoic crustal thickening, due to the Brasiliana Orogenia, which also produced the migmatite features frequently observed in these rocks. The formation of the igneous bodies and the placement of the magma that generated them occurred in at least two instants of magmatic ascension. The first pulse formed the protolith of the metagranitoid body that was later deformed by the effect of the regional metamorphism acting on the nesting gneisses of the Tamboril-Santa Quitéria complex. They were, therefore, associated to the Brazilian intrusive suite without the tardi-orogenic that occurs in the Borborema Province with ages from 620 to 580 Ma (Bizzi et al, 2003). The second moment of magmatic ascent was responsible for the formation of Pajé granite, 522 ± 12 Ma (Tavares Júnior, 1992), which, as observed in SRTM image, shows structural segments of the terrain. An early injection of the magma forming the Pajé Granite may have generated the biotite sienogranite Tamboril - Santa Quitéria, since the two have similar mineralogical and petrographic features, such as the same sienogranitic composition, the presence of mafic autolytes and a similar proportion of accessory minerals, such as biotite.